Leukocyte-Reduced Platelet-Rich Plasma Treatment of Basal Thumb Arthritis: A Pilot Study. (5th July 2016) - Loibl, Markus; Lang, Siegmund; Dendl, Lena-Marie; Nerlich, Michael; Angele, Peter; Gehmert, Sebastian; Huber, Michaela
Abstract : A positive effect of intra-articular platelet-rich plasma (PRP) injection has been discussed for osteoarthritic joint conditions in the last years. The purpose of this study was to evaluate PRP injection into the trapeziometacarpal (TMC) joint. We report about ten patients with TMC joint osteoarthritis (OA) that were treated with 2 intra-articular PRP injections 4 weeks apart. PRP was produced using the Double Syringe System (Arthrex Inc., Naples, Florida, USA). A total volume of 1.47 ± 0.25 mL PRP was injected at the first injection and 1.5 ± 0.41 mL at the second injection, depending on the volume capacity of the joint. Patients were evaluated using VAS, strength measures, and the Mayo Wrist score and DASH score after 3 and 6 months. VAS significantly decreased from 6.2 ± 1.6 to 5.4 ± 2.2 at six-month follow-up (P < 0 . 05 ). The DASH score was unaffected; however, the Mayo Wrist score significantly improved from 46.5 ± 18.6 to 67.5 ± 19.0 at six-month follow-up (P = 0 . 05 ). Grip was unaffected, whereas pinch declined from 6.02 ± 2.99 to 3.96 ± 1.77 at six-month follow-up (P < 0 . 05 ). We did not observe adverse events after the injection of PRP, except one occurrence of a palmar wrist ganglion, which resolved without treatment. PRP injection for symptomatic TMC OA is a reasonable therapeutic option in early stages TMC OA and can be performed with little to no morbidity.